Safety Profile and Adverse Events Associated with Repeated Epidural Steroid Injections in Chronic Low Back Pain: A Retrospective Study - Prakash, Pulkit; Verma, Shweta; Kumar, Pramod (Journal of Neonatal Surgery, 2025)
Background: Chronic low back pain (CLBP) remains one of the most prevalent causes of disability around the world. Epidural steroid injections (ESIs) are commonly employed to alleviate persistent symptoms, and multiple injections are sometimes performed when pain recurs or persists. Nonetheless, there are ongoing concerns regarding the safety of repeated ESIs, including possible infections, neurologic compromise, and systemic steroid-related effects. Methods: In this retrospective investigation, patient records from a tertiary care hospital were reviewed to identify adults with CLBP who underwent at least two lumbar ESIs within a single year. We noted demographic data, the total number of injections, the time between injections, and both immediate (e.g., vasovagal responses) and delayed (e.g., infections, neurologic deficits) adverse events. Descriptive statistics were used to characterize the patient population, and we compared the frequency and nature of adverse events relative to the number of injections. Results: A total of 250 patients (mean age 52.4 ± 11.2 years, 62% female) met the inclusion criteria. On average, participants received 2.7 ± 0.4 injections over the study period. Forty-eight patients (19.2%) experienced at least one adverse event, of which 67% were mild and self-limiting (e.g., short-term headache, localized injection-site discomfort). More severe complications—such as infection or transient neurological deficits—occurred in 2.8% of the cohort, predominantly among those who underwent more than three injections. No irreversible neurologic harm or life-threatening infections were identified. Conclusion: These findings indicate that repeated ESIs for CLBP can generally be performed with an acceptable safety margin in carefully selected patients. However, the likelihood of adverse events appears to increase with the total number of injections. Clinicians must balance the analgesic benefits of repeated ESIs against potential complications, especially in individuals requiring multiple procedures.